The effect of Seprafilm on adhesion formation and tendon healing after flexor tendon repair in chicken - Yilmaz, Erhan; Avci, Mustafa; Bulut, Mehmet; Kelestimur, Halidun; Karakurt, Lokman; Ozercan, Ibrahim (My University, 2010)
Adhesion of the tendon, which can occur during healing of tendon repair, is negatively affected by the outcome of surgery. In this experimental study, we sought to prevent adhesion of the tendon, and determined the mechanical stiffness of repair tissue by wrapping sodium hyaluronate and carboxymethylcellulose (Seprafilm; Genzyme, Cambridge, Massachusetts) around the repaired tendon segments. The study group comprised 2 groups of 20 chickens. In group I, the right gastrocnemius tendons of the chickens were cut smoothly, and after tendon and sheath repair, the skin was sutured. In group II, the right gastrocnemius tendons of the chickens were cut, the tendons were repaired, and before skin closure, Seprafilm was wrapped around the repaired tendon segments. Plastic splints were used for holding the chickens' ankles in a neutral position, and they were allowed weight bearing for 8 weeks. In group II, anatomic space between the tendon-sheath and tendon was clear and the tendon-sheath complex was sliding easily around the repaired tendon segment, and this complex was more functional both biomechanically and histologically. Also, the Seprafilmapplied tendons (group II) were observed to be biomechanically more resistant to the tensile forces in group I. Seprafilm is an easily applied interpositional material that can be used safely to prevent adhesion during the tendon healing process.
Keywords: Animals; Bandages; Chickens; Hyaluronic Acid; Tendon Injuries; Tenotomy; Tissue Adhesions; Treatment Outcome; Wound Healing; carboxymethylcellulose; hyaluronic acid; hyaluronic acid; seprafilm; adhesion barrier film; hyaluronic acid; animal experiment; animal model; animal tissue; ankle; article; biomechanics; chicken; controlled study; experimental study; flexor tendon; flexor tendon injury; functional assessment; gastrocnemius muscle; histopathology; nonhuman; postoperative complication; splint; tendon; tendon adhesion; tendon reconstruction; tendon sheath; tensile strength; weight bearing; wound healing; animal; bandage; pathology; tendon injury; tenotomy; tissue adhesion; treatment outcome; wound healing; complication; pathology; Tendon Injuries; tenotomy; Tissue Adhesions